1998
DOI: 10.1046/j.1365-2362.1998.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole and dilazep suppress oxygen radicals in puromycin aminonucleoside nephrosis rats

Abstract: DPM and DZ scavenge hydroxyl radicals, thereby alleviating PAN nephrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Increased lipid peroxidation has also been measured in glomeruli from humans with congenital nephrotic syndrome of the Finnish type [32]. Further evidence in support of this potential mechanism includes studies demonstrating that treatments commonly used to treat nephrotic syndrome in humans, such as glucocorticoids and other immunosuppressants, can increase glomerular AOE and protect against PAN-induced injury [12,14], studies showing that AOE or antioxidants can ameliorate the effects of PAN [28,29,33,34] and that inhibition of AOE exacerbates PAN nephrosis [35]. A metabolite of PAN has also previously been shown to be converted by glomeruli to hypoxanthine, a component of the xanthine/hypoxanthine pathway for the production of superoxide radicals [36].…”
Section: Discussionmentioning
confidence: 99%
“…Increased lipid peroxidation has also been measured in glomeruli from humans with congenital nephrotic syndrome of the Finnish type [32]. Further evidence in support of this potential mechanism includes studies demonstrating that treatments commonly used to treat nephrotic syndrome in humans, such as glucocorticoids and other immunosuppressants, can increase glomerular AOE and protect against PAN-induced injury [12,14], studies showing that AOE or antioxidants can ameliorate the effects of PAN [28,29,33,34] and that inhibition of AOE exacerbates PAN nephrosis [35]. A metabolite of PAN has also previously been shown to be converted by glomeruli to hypoxanthine, a component of the xanthine/hypoxanthine pathway for the production of superoxide radicals [36].…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies suggest the involvement of reactive oxygen species (ROS), such as superoxide or hydroxyl radicals, in the disease pathogenesis [1,2,3,4,5,6,7,8,9,10]. Isolated glomeruli from these rats show increases in luminol-amplified chemiluminescence [1,2] and elevated malondialdehyde levels [3,4,5,6,7]. Chaverri et al [3] reported that the nephrotic syndrome induced by PAN was ameliorated by a-tocopherol supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, podocytes receiving SPE, SalB, RA and TAC had lower ROS production than the PAN group. It has been known that ROS is one of the major pathogenic causes of oxidative stress in PAN nephrosis, and the glomerular injury is acutely mediated by the overproduction of ROS [4], which then may interact with biomolecules, including DNA, resulting in potentially deleterious cellular consequences [6]. A large number of signaling pathways appear to be regulated by ROS, particularly with regard to the regulation of differentiation, apoptosis and proliferation [30].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have demonstrated that PAN-induced glomerular injury is acutely mediated via the overproduction of reactive oxygen species (ROS) [4,5]. …”
Section: Introductionmentioning
confidence: 99%